Expert reviews, peer recommendations and buying red wine: experimental evidence. (3rd April 2019) - Thrane, Christer
ABSTRACT: The micro level behavioral foundation for how quality reviews of experts and word of mouth (WOM) affect demand for experience goods has received scant attention in previous research. Taking an experimental approach, the present study examines how quality reviews and peer recommendations influence consumers' decisions to buy red wine. Four main findings are presented for a sample of Norwegian wine consumers. First, consumers prefer wines that have obtained very good quality reviews to wines getting OK quality reviews. Second, consumers prefer peer-recommended wines to non-recommended wines. Third, the effect of a very good quality review is greater for non-recommended wines than for peer-recommended wines. Fourth, some of these effects on wine buying decisions are contingent on price level, and there is also some heterogeneity to their magnitude. The results are mainly in concert with the proposed hypotheses.